2011
DOI: 10.3109/0142159x.2011.540270
|View full text |Cite
|
Sign up to set email alerts
|

Integration of e-learning resources into a medical school curriculum

Abstract: It should not be assumed that all students will choose to use an e-learning resource in the same way and instructional design should enable alternative approaches. The sequence in which the e-learning resource is used in relation to the other learning opportunities, such as lectures and PBL group discussions, may be important and merits further consideration. The experiences reported in this study provide encouragement and pointers for others engaged in the integration of e-learning in their curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 10 publications
3
69
0
2
Order By: Relevance
“…In conjunction with this result, Khogali et al (2011), in their study, reported that students found animation, video, and self-assessment sections more useful, but indicated that a discussion forum should be included in an online learning content. While some of these issues have been addressed in the current study, namely the inclusion of the case studies for discussion, students' comments indicate that the content remains too stagnant for their liking.…”
Section: It Was Great To Have a Look At And Repeat The Courses Againmentioning
confidence: 84%
See 2 more Smart Citations
“…In conjunction with this result, Khogali et al (2011), in their study, reported that students found animation, video, and self-assessment sections more useful, but indicated that a discussion forum should be included in an online learning content. While some of these issues have been addressed in the current study, namely the inclusion of the case studies for discussion, students' comments indicate that the content remains too stagnant for their liking.…”
Section: It Was Great To Have a Look At And Repeat The Courses Againmentioning
confidence: 84%
“…According to Khogali, Davies, Donnan, Gray, Harden, Mcdonald, Pippard, Pringle, and Yu (2011), blended learning environments can be implemented successfully alongside the conventional learning methods in an existing medical curriculum. In addition, the online learning sources generated with cooperation among medical schools can be integrated into a local curriculum.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…With exponential expansion of IT, the field of medical education has also embraced innovative electronic learning (e-learning) techniques (1) . Benefits of elearning on the performance of medical students have been demonstrated in Western (2) as well as in Asian countries (3) with the latter group of researchers demonstrating the effectiveness of e-learning activity on the results of education of Biochemistry (3) ; a basic science taught during the first year of medical school.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Despite the advances in online technologies, it is recognized that medicine is a competency-based discipline and it is not desirable to fully replace traditional medical education with online learning. [4] Attempts have been made to blend E-learning technology with traditional instructor-led training. [5] Increasingly, there are concerns about how both traditional and online teaching can be combined for effective "blended" learning.…”
Section: Introductionmentioning
confidence: 99%